Linguistic Differences between the Terms “Khabar” and “Naba'” (A Semantic Study of Words in the Qur'an): Perbedaan Linguistik antara istilah “Khabar” dan “Naba’ ” (Studi Semantik Kata-Kata Al-Qur'an) - Rowiyah; Ahmad Zuhri; Harun Al Rasyid (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The Qur’an, as a central religious text, employs linguistic precision in conveying divine messages. Specific background: Among the vocabulary used, the terms Al-Khabar and Al-Nabāʾ are often considered synonymous but contain nuanced differences that impact interpretation. Knowledge gap: Existing studies overlook the semantic and contextual distinctions between these two terms in Qur’anic discourse. Aims: This study aims to analyze the linguistic and semantic differences between Al-Khabar and Al-Nabāʾ through a qualitative approach using semantic and comparative methods. Results: The research reveals that while both terms relate to the concept of “news” or “information,” Al-Nabāʾ specifically refers to information that is highly important, beneficial, and carries profound implications, whereas Al-Khabar lacks such mandatory characteristics. Novelty: This study uniquely highlights that Al-Nabāʾ must fulfill three specific criteria—importance, utility, and the ability to produce knowledge or certainty—making it more exclusive in its Qur’anic application. Implications: These findings contribute to deeper Qur’anic linguistic studies and assist interpreters in making more accurate semantic distinctions, thus enhancing the integrity of exegesis and linguistic analysis of the Qur’an.Highlight : The study focuses on the differences in meaning between Al-Khabar and Al-Nabāʾ in the Qur'an. Al-Nabāʾ has specific characteristics: it is important, useful, and generates knowledge. It uses a descriptive and comparative approach based on literature studies. Keywords : Al-Khabar, Al-Nabāʾ, Synonym, Semantic, Qur'an